Bioinspired honeycomb sandwich structures for enhanced hail impact resistance - Solak, Alparslan (TAYLOR & FRANCIS INC, 2025)
The study explores the mechanical behavior of bioinspired honeycomb sandwich structures against hail impact using Ls-Dyna. The hail model, based on experimental values, is created with smoothed particle hydrodynamics. The force-time graph aligns with the peak value from the impact test on a rigid bar, showing good agreement with literature. The sandwich model, impacted by a hemispherical-nosed impactor, exhibits post-impact damage images and collapse in the z-axis consistent with experimental results. Diversified honeycomb cell profiles include wavy, spider web, bamboo, and combinations. When subjected to hail impact, the wavy model excels in sEA, spider web-bamboo in specific deformation, and bamboo in sPCF.
Keywords: Honeycomb; sandwich; sEA; sPCF; bioinspiration; hail impact; Ls-Dyna; Materials Science; Mechanics